PHILOSOPHICAL VALUES OF THE TAPAI PARTY TRADITION IN SOCIETY - Wahyu, Rekka; Nasution, Hasan Bakti (JURNAL SOCIUS, 2024)
This research aims to reveal the philosophical values contained in the Tapai Festival, which include religious, social, economic, local wisdom and cultural identity values. Using a qualitative method with an ethnographic approach, data was collected through participant observation and in-depth interviews with traditional leaders and local communities. The research results show that the Tapai Festival not only strengthens community solidarity, but also becomes a means to teach the younger generation about the importance of maintaining traditions and ancestral heritage. These values are reflected in every stage of the ceremony, from preparation to implementation, which is full of symbolism and deep meaning. Thus, the Tapai Festival tradition plays an important role in preserving the philosophical values of the Batubara people and enriching Indonesia's cultural treasures.